(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
In this work the effect of porphyrines, AgTOEtPyP, on the cell population kinetics was studied in vitro using morphological and biochemical techniques. The results suggested that AgTOEtPyP action consisted in the simultaneous suppression of the cell growth and activation of the cell death. About 40% of the cells were shown to die via apoptotic pathway. So, the porphyrin studied may be attributed to inducers of both necrotic and apoptotic processes. The results obtained support our previous assertion that AgTOEtPyP may be considered as a potential chemotherapeutic agent.